ANÁLISE QUALITATIVA DA PERCEPÇÃO DE CONFORTO TÉRMICO E CONSUMO ENERGÉTICO DE SALAS COMERCIAIS EM BELÉM-PA - Souza, Kamilla; Maués, Luiz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The high consumption of electric energy in residential and commercial buildings has reached 47% of the total energy used in the country, mainly due to the excessive use of artificial lighting and air conditioning systems. In this context, the thermal comfort and energy consumption are fundamental in places with a high thermal sensation, such as in the city of Belém, with equatorial climate and responsible for more than 30% of the energy used in Pará. This study aims to analyze the perception of thermal comfort in commercial rooms and the perception of users in relation to this with energy consumption, both considering different service stations positions. For this, questionnaires were applied in 14 rooms with 4 projects, including 33 participants, the results showed the relation between energy consumption and thermal comfort and, consequently, the influence of this relation in employee productivity.